THE TEHRAN SUMMIT, OR THE RUSSIAN PRESIDENT’S VISIT TO IRAN - LUKOIANOV, Alexander (CENTRAL ASIA AND THE CAUCASUS, 2008)
On 16 October, 2007, Tehran hosted the second summit of the Caspian states attended by Russia, Azerbaijan, Turkmenistan, Kazakhstan, and Iran. The importance of this international event is thrown into bolder relief by the failure (recognized as such by observers and analysts, as well as the leaders of the countries involved) of the first Caspian summit convened in Ashghabad in April 2002, at which the participants agreed on few issues and failed to arrive at an agreed final document.In 2002, the world and regional situation were very different; three of the countries were headed by different people: Iran, by Mohammad Khatami; Azerbaijan, by Heydar Aliev; and Turkmenistan, by Saparmurat Niyazov.They got together in the capital of Turkmenistan to discuss the Caspian’s status and the way its water area and the natural reserves should be divided—issues that surfaced when the Soviet Union died and the littoral Soviet Union republics became independent. In Soviet times, they shared the Caspian’s reserves with all the other people of a single state. The Soviet Union’s disintegration created numerous border problems; the fuel- and fish (mainly sturgeon)-rich Caspian acquired its share of post-Soviet problems.The Iranian leaders, for example, were out to capitalize on this in order to claim larger share of the Caspian than before: they argued that, under the new conditions, the water body should be divided into five equal parts. The post-Soviet states, however, refused to accept this. They insisted that the national zones should correspond to the lengths of the littoral line. In this case Kazakhstan would have received 28 percent; Russia, 18 to 19 percent; Turkmenistan, 19 percent; Azerbaijan, 21 percent, and Iran (along the Huseynkali-Astara line), 11.4 to 13 percent. Tehran preferred to look at the Caspian as a lake to be divided, in full accordance with international law, into equal shares (20 percent each). Iran also argued that it should get 50 percent of the Caspian, since the former Soviet republics, which appropriated the Soviet state’s rights and shouldered its duties, should be satisfied with the other half.